STRATEGI PENANGANAN BENCANA TANAH LONGSOR DI JALUR PARIWISATA HUTAN PUSUK KECAMATAN PEMENANG KABUPATEN LOMBOK UTARA: PENDEKATAN RISIKO DAN TINDAKAN PREVENTIF - Sayfuddin, Sayfuddin (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
ABSTRACT Landslide Disaster Management Strategy Landslides along the Pusuk forest tourism route, Pemenang District, West Lombok Regency, are very important to reduce the risks and impacts caused. This area, which consists of hills and steep slopes, is very prone to landslides, especially when rainfall is high. From the results of research on the causal factors, in the landslide disaster management strategy at the research location, where data was obtained through questionnaires and analyzed using validity and reliability tests using SPSS Software, researchers can conclude the following: The factors causing landslides vary, but in this study, several main factors have been identified. soil type 90.67%, High rainfall 89.33%, additional load on slopes 88.67%, inappropriate land use 88.00%, and vibrations due to earthquakes are the main factors that increase the risk of landslides 87.33%. For disaster risk management strategies, the proposed steps include increasing community understanding through counseling on landslides, strengthening slope infrastructure with terracing, installing retaining walls, and improving drainage systems to prevent erosion. Proper land use planning must also be implemented to reduce pressure on vulnerable slopes. In addition, cooperation is needed between the government, community, and private sector to ensure that the management strategy program runs effectively and sustainably. With this approach, it is hoped that the risk of landslides along the Pusuk tourist route can be minimized.